The Impact of Academic Feedback and Teacher Relationships on Self-Efficacy: The Mediating Role of Academic Motivation - Aizaz Haider; Munazza Hayat; Fatima Zafarullah, (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2024)
The purpose of this research is to examine the impact of academic feedback on students' self-efficacy. Additionally, the study investigates the effect of teacher-student relationships on self-efficacy. A further objective of this research is to explore the mediating role of academic motivation in the relationship between academic feedback, teacher relationships, and self-efficacy. The research adopts a quantitative design and is grounded in a positivist philosophy, emphasizing objective data and statistical analysis. A deductive research approach was employed to test the proposed hypotheses. The study population consisted of students enrolled at Thal University Bhakkar, with a total population size of 6,000 students. A sample size of 300 students was selected using a simple random sampling technique to ensure representativeness and minimize bias. Data were collected using structured survey questionnaires, and the analysis was conducted using SPSS. This research holds practical significance as it offers actionable recommendations for educators, schools, and policymakers. By focusing on constructive feedback, fostering positive teacher-student relationships, and enhancing students' motivation, institutions can improve students' academic performance and overall confidence.